Repeated delivery of chlorhexidine chips for the treatment of peri‐implantitis: A multicenter, randomized, comparative clinical trial. Issue 1 (11th November 2020) - Machtei, Eli E.; Romanos, Georgios; Kang, Philip; Travan, Suncica; Schmidt, Stephan; Papathanasiou, Evangelos; Tatarakis, Nikolaos; Tandlich, Moshik; Liberman, Leila H.; Horwitz, Jacob; Bassir, Seyed Hossein; Myneni, Srinivas; et al.
Abstract: Background: Peri‐implantitis is a challenging condition to manage and is frequently treated using non‐surgical debridement. The local delivery of antimicrobial agents has demonstrated benefit in mild to moderate cases of peri‐implantitis. This study compared the safety and efficacy of chlorhexidine gluconate 2.5 mg chip (CHX chips) as an adjunctive treatment to subgingival debridement in patients afflicted with peri‐implantitis. Methods: A multicenter, randomized, single‐blind, two‐arm, parallel Phase‐3 study was conducted. Peri‐implantitis patients with implant pocket depths (IPD) of 5‐8 mm underwent subgingival implant surface debridement followed by repeated bi‐weekly supragingival plaque removal and chlorhexidine chips application (ChxC group) for 12 weeks, or similar therapy but without application of ChxC (control group). All patients were followed for 24 weeks. Plaque and gingival indices were measured at every visit whereas IPD, recession, and bleeding on probing were assessed at 8, 12, 16, 24 week. Results: A total of 290 patients were included: 146 in the ChxC group and 144 in the control. At 24 weeks, a significant reduction in IPD ( P = 0.01) was measured in the ChxC group (1.76 ± 1.13 mm) compared with the control group (1.54 ± 1.13 mm). IPD reduction of ≥2 mm was found in 59% and 47.2% of the implants in the ChxC and control groups, respectively ( P = 0.03). Changes in gingival recession (0.29 ± 0.68 mm versus 0.15 ± 0.55 mm, P = 0.015) and relative attachment gain (1.47 ± 1.32 mm and 1.39 ± 1.27 mm, P = 0.0017) were significantly larger in the ChxC group. Patients in the ChxC group that were < 65 years exhibited significantly better responses ( P < 0.02); likewise, non‐smokers had similarly better response ( P < 0.02). Both protocols were well tolerated, and no severe treatment‐related adverse events were recorded throughout the study. Conclusions: Patients with peri‐implantitis that were treated with an intensive treatment protocol of bi‐weekly supragingival plaque removal and local application of chlorhexidine chips had greater mean IPD reduction and greater percentile of sites with IPD reduction of ≥2 mm as compared with bi‐weekly supra‐gingival plaque removal.